Geotecnologia aplicada ao estudo das artes fixas da pesca artesanal na zona costeira do Baixo Sul da Bahia e Recôncavo baiano - Souza, Ivonice Sena de (2018)
Artisanal fishing is gaining prominence in the world scenario and is responsible for much of the fish production, especially in the tropical regions. The small-scale fishing industry benefits little from geotechnology. The objective of this work was to test the use of geotechnologies in the study of fixed fishing gears in the Coastal Zone of the Southern Bahia and RecôncavoBaiano Regions. We used high resolution remote sensing images of Google Earth in the identification, mapping, classification and measurement of fixed fishing gear, specifically the fishing rods and the fishing grounds. The structures of these fishing gear have been identified in the best available images and flagged with the Google Earth markers. In the Southern Lowlands, 152 camboas were identified. In the RecôncavoBaiano Region, 589 fixed fishing gears were identified for two different types of fishing gear, the fishing fence and the V-shaped cambo. 163 camboas were located in the area of the Marine Extractive Reserve of Bay of Iguape and 426 fishing grounds in the western region of the Bay of All Saints. From the images of Google Earth, it was possible to identify 16 types (different arrangements of the components, with recurrent geometries) for the Southern Lowlands. For the study area of the Lower South, to facilitate the structuring of the data, the area was subdivided into three subareas. For the subarea two were conducted semi-structured interviews with fishermen and camboas owners for the characterization of fishing and the different types of shrimp. There was also the follow-up of some fisheries (fishing) of shrimp. The structures of some samples of the fixed fishing gear types were measured, considering the following measures: the maximum length of the spy the entrance of the room, hallway or camarinha. The use of Google Earth images has enabled a good result in the identification, mapping, classification and measurement of fixed gears of artisanal fishing. The results show that the recent advances in geotechnology and the free access to high resolution satellite images have great potential for aid in the process of recognition and delimitation of artisanal fisheries, as well as in the study of fixed fishing gear, the use of natural resources and the occupation of marine and coastal areas by fishing activity.